Diagnostic work-up for detection of paroxysmal atrial fibrillation after acute ischemic stroke: cross-sectional survey on German stroke units - Rizos, Timolaos; Quilitzsch, Anika; Busse, Otto; Haeusler, Karl Georg; Endres, Matthias; Heuschmann, Peter; Veltkamp, Roland (Stroke, 2015)
Background and Purpose—Multiple methods to detect paroxysmal atrial fibrillation (pAF) in patients with acute stroke are available. However, it is unknown which approaches are currently used in clinical routine and guidelines remain vague to the extent of cardiac monitoring. We characterize diagnostic efforts for pAF detection on German stroke units (SU).Methods—A standardized anonymous questionnaire was sent to all clinical leads of certified SUs in Germany. The questionnaire focused on basic characteristics of SUs, procedures to detect AF, and estimates on AF detection.Results—One hundred seventy-nine SU leads participated (response rate 71.6%). All patients undergo continuous bedside ECG monitoring. A percentage of 77.6 SUs initiate additional 24-hour Holter ECG in >50% of patients without known AF. Patients with transient ischemic attack are monitored significantly shorter than patients with ischemic stroke. Independent of SU type or size, 67.6% of leads assumed to fail detecting pAF in 5% to 20% of patients. In cryptogenic stroke, additional ECG monitoring is recommended by 90.2% but only 13.8% of SUs perform routine ECG follow-up visits. The use of implanted event recorders is low (1-10 patients/y by 60.7% of SUs; 28.1%: no use). A percentage of 83.9 do not use external event recorders.Conclusions—Our survey demonstrates substantial heterogeneity among German SUs on diagnostic work-up for pAF. Future prospective multicenter studies should systematically evaluate the impact of different methods to uncover pAF.
Gesehen am 25.06.2020